Reviewing the transparency of the accounting process in the claretian congregation - Yolinda Yanti Sonbay; Beatrix Yunarti Manehat; Egidius Taimenas (Institute of Computer Science (IOCS), 2023)
The research data was taken by means of documentation and in-depth interviews. Data analysis used epoch, phenomenological reduction, imagination variation, and synthesis of meaning and essence techniques.The research results show that transparency is implemented in the accounting process in the Claretian Congregation. This transparency is reflected in two main things, namely there is a General Accounting Plan that regulates all procedures, rules and accounting processes of the Congregation. Furthermore, there is a Profit and Loss Report and Balance Sheet which can be accessed by all related parties.Transparency is carried out because the Congregation is committed to maintaining the trust of partners, bringing prosperity to the people according to the Catholic mission and more than that, first and foremost is being responsible to God.There are 3 main values of the Congregation which are embodied in the transparency of financial management, namely Prioritizing group interests, Avoiding individualism and Referring to poverty. All financial management must be transparent because it is centered, from, by and for God. The congregation maintains the mission of the catholic church: become a channel of God's blessings through joyful service to others. Exercising Transparency means honoring God.The contribution of this research is that Catholic values reflected in congregational values are the basis for enforcing transparency in the accounting process, which in the business world is full of secular values.